Acute Liver Failure in a Patient With Dengue Shock Syndrome. Issue 4 (7th April 2020) - Lewis, Justin; Mitra, Arnab; Chang, Michael
ABSTRACT: Dengue is an arboviral disease of significant burden in tropical countries. It commonly affects the liver, ranging in presentation from asymptomatic transaminitis to acute liver failure. We present a young woman from India who developed acute liver failure because of dengue shock syndrome and improved without a liver transplant. We review the disease characteristics and management of dengue, with a focus on the natural history of illness and how to approach the possible need for liver transplant in these patients.